Analisa Pentingnya Pemberian Imunisasi Dasar Lengkap Pada Bayi dan Balita di Wilayah Kerja UPTD Puskesmas Patek - Diana Lestari; Kiki Rezeki Amelia (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Each immunization program has an analytical goal to reduce the incidence of disease and mortality due to diseases that can be prevented by immunization (PD3I). Currently, these diseases are dysentery, tetanus, whooping stone (pertussis), smallpox (measles), polio, and tuberculosis. Immunization is the most effective primary prevention of infectious diseases. Immunization protects individuals from serious diseases and prevents the spread of infectious diseases. Immunization is one of the efforts to increase immunity and eradicate infectious diseases. Providing immunization to infants and toddlers can increase immunity. Based on the results of the survey that has been conducted, there are still infants and toddlers in Ujong Rimba Village who have not received complete basic immunization due to the lack of knowledge of mothers regarding the importance of complete basic immunization, as well as the fear of mothers regarding the side effects that arise after infants and toddlers are immunized. The purpose of this community service is to increase public knowledge about the benefits and negative impacts of not carrying out complete basic immunization. This community service activity was carried out on November 11, 2024 at the Ujong Rimba Hall Building, Darul Hikmah District, which was attended by 27 people. The results of this counseling or education can increase knowledge for the people of Ujong Rimba Village about the benefits of complete basic immunization injections for babies and toddlers.